Non-Motor Symptoms as Predictors of Quality of Life in Egyptian Patients With Parkinson’s Disease: A Cross-Sectional Study Using a Culturally Adapted 39-Item Parkinson’s Disease Questionnaire - Shalash, Ali S.; Hamid, Eman; Elrassas, Hanan Hani; Bedair, Ahmed Safwat; Abushouk, Abdelrahman Ibrahim; Khamis, Mohamed; Hashim, Mostafa; Ahmed, Nahed Salah-Eldin; Ashour, Samia; Elbalkimy, Mahmoud (Frontiers in Neurology, 2018)
Objective: The prevalence of non-motor symptoms (NMSs) and their impact on health-related quality of life (HRQoL) in Parkinson's disease (PD) has been reported inconsistently among different populations. In this study, we aimed to investigate the NMSs and HRQoL profiles and their correlations in Egyptian PD patients, using a culturally adapted Arabic version of the 39-item Parkinson’s disease questionnaire (PDQ-39)). Methods: Ninety-seven PD patients were rated using the Unified Parkinson's Disease Rating Scale (UPDRS), the Non-Motor Symptoms Scales (NMSS), Beck Depression Inventory (BDI), and the Arabic version of PDQ-39. We used the Spearman’s rank correlation and multiple linear regression analyses to evaluate the relationship between NMSs domains and HRQoL dimensions. Results: Fatigue/sleep (91.3%) and mood/cognitive disturbances (87%) were the most frequently and severely affected NMSS domains. Other NMSs included urinary (75.9%), memory/attention (72.4%), gastrointestinal (67.8%), and cardiovascular problems (64.8%). The total NMSS scores were positively correlated with UPDRS I, II, and III scores. Depression assessed by BDI was prevalent in 76.7% of PD patients. Moreover, Aall enrolled PD patients reported impairment in different HRQoL dimensions, especially mobility (98.9%), activities of daily living (97.8%) and emotional well-being (95.5%). The summary index of PDQ-39 (PDQ-SI) was correlated to the total NMSS, UPDRS-I, UPDRS-II Off, UPDRS-III (Off and On states) and BDI scores. Conclusion: This study showeds the high prevalence of NMSs and the value of NMSS and BDI scores as predictors of HRQoL inof Egyptian PD patients. Therefore, Identifying characterizing the NMSsnon-motor profile is essential for tailoring management strategies offor PD patients.